Determinants of Use Behavior in Utilizing Fintech Investment Management for Gen-Z - Kadek Gita Saraswati; Ni Made Dwi Ratnadi; I Putu Sudana; Eka Ardhani Sisdyani (Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze behavioral intention and use behavior in using fintech investment management through the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, namely performance expectancy, effort expectancy, social influences, facilitating conditions, hedonic motivation, price values and habits. This study used quantitative approach. The population in this study were all Generation Z in Bali which determine using convenience sampling method. The data analysis technique in this research is multiple regression using Smart-pls software. The results of the analysis provide evidence that performance expectancy, social influences, facilitating conditions, hedonic motivation and habits had positive effect on behavioral intention in using fintech investment management. In addition, behavioral intention had a positive effect on the use behavior of using fintech investment management.